Identifikasi Tahap Perkembangan Mikrospora melalui Ukuran Floret pada Jantung Pisang Tanduk - Pagalla, Devi Bunga; Ahmad, Jusna; Husain, Indriati; Lamante, Nazwa S.; Eyato, Rika (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to identify the relationship between floret length and the developmental stages of microspores in banana male inflorescence (Musa spp. cv. Tanduk), and to determine the optimal floret size range as an explant source for initiating microspore culture. Ten bract layers were analyzed, with five florets randomly selected from each layer and measured for their length. Anthers were extracted from each floret, crushed in sterile water, and observed microscopically using a wet mount preparation. The results revealed a strong correlation between floret length and microspore developmental stages. Microspores at the late uninucleate (vacuolated) to early bicellular stages were consistently found in florets ranging from 4.68 to 4.34 cm in length. Based on these findings, florets within the 4.60 to 4.00 cm range are recommended as the optimal size for microspore culture initiation, as they contain a higher proportion of developmentally competent microspores for embryogenesis induction. In conclusion, this study provides essential morphological and cytological criteria to support efficient explant selection for in vitro regeneration of banana through the microspore culture approach.